Towards closing the nitrogen flow in UK agriculture: An explorative study of integrated food and bioenergy production with increased nitrogen recirculation - Skenhall, Sara Alongi (My University, 2011)
Nitrogen is an essential growth factor in nature and for food production. It exists in many forms, including reactive nitrogen compounds available for plant uptake, that can cause environmental impacts in high concentrations. Large amounts of reactive nitrogen in fertilisers are applied to crop areas, and the anthropogenic use of reactive nitrogen has increased manifold during the last century. Nitrogen in harvest residues and animal manure is recycled to crop fields ineffieciently, and the overall flow of nitrogen through agriculture is practically linear, with substantial losses to air and water. Policies regulate some nitrogen practices, but seem not to provide a strong incentive for recycling. A more closed ow of reactive nitrogen within agriculture and the rest of society could reduce the need for nitrogen fertilisers, and also reduce environmental impacts caused by nitrogen leaching, notably eutrophication of aquatic ecosystems. Pressure is also put on agriculture to meet the increased demand for bioenergy. Increased production of cellulosic bioenergy crops can, in this context, have a positive effect on the environmental performance of agriculture, and can in several ways be part of strategies for obtaining a more closed flow of nitrogen in the socio-agricultural system. This thesis develops and models an alternative agricultural system, with increased nitrogen recirculation. Cultivation of cellulosic bioenergy crops are integrated into the food production to provide nitrogen leaching interception. These biomass production systems are combined with nitrogen recycling. Livestock are fed more efficiently than in the current system. Manure is collected and treated through anaerobic digestion for production of biogas and stabilisation of volatile nitrogen. Analyses using a model representation of the alternative agricultural system show that these measures substantially improve the recycling of nitrogen in the system, reduce the losses and decrease the need for chemical fertiliser input. The thesis concludes that implementation of certain bioenergy options that enhance nitrogen recycling can give an important contribution to closing the nitrogen flow in agriculture. A second conclusion is that a systems perspective on nitrogen is essential for implementation of policies promoting an increased nitrogen recycling within the socio-agricultural system.
Keywords: Energi; Hållbar utveckling; Miljöteknik; Övrig annan teknik; Energy; Sustainable Development; Environmental engineering; Other Engineering and Technologies not elsewhere specified